A New Glycogen Storage Disease Caused by a Dominant PYGM Mutation. Issue 2 (3rd June 2020) - Echaniz‐Laguna, Andoni; Lornage, Xavière; Laforêt, Pascal; Orngreen, Mette C.; Edelweiss, Evelina; Brochier, Guy; Bui, Mai T.; Silva‐Rojas, Roberto; Birck, Catherine; Lannes, Béatrice; Romero, Norma B.; Vissing, John; et al.
Abstract : Objective: Glycogen storage diseases (GSDs) are severe human disorders resulting from abnormal glucose metabolism, and all previously described GSDs segregate as autosomal recessive or X‐linked traits. In this study, we aimed to molecularly characterize the first family with a dominant GSD. Methods: We describe a dominant GSD family with 13 affected members presenting with adult‐onset muscle weakness, and we provide clinical, metabolic, histological, and ultrastructural data. We performed exome sequencing to uncover the causative gene, and functional experiments in the cell model and on recombinant proteins to investigate the pathogenic effect of the identified mutation. Results: We identified a heterozygous missense mutation in PYGM segregating with the disease in the family. PYGM codes for myophosphorylase, the enzyme catalyzing the initial step of glycogen breakdown. Enzymatic tests revealed that the PYGM mutation impairs the AMP‐independent myophosphorylase activity, whereas the AMP‐dependent activity was preserved. Further functional investigations demonstrated an altered conformation and aggregation of mutant myophosphorylase, and the concurrent accumulation of the intermediate filament desmin in the myofibers of the patients. Interpretation: Overall, this study describes the first example of a dominant glycogen storage disease in humans, and elucidates the underlying pathomechanisms by deciphering the sequence of events from the PYGM mutation to the accumulation of glycogen in the muscle fibers. ANN NEUROL 2020;88:274–282.